PENGARUH PENGETAHUAN TENTANG PERBANKAN SYARI’AH DAN DISPOSABLE INCOME TERHADAP MINAT MENABUNG PADA BANK BNI SYARI’AH KANTOR CABANG SUDIRMAN PEKANBARU - Kalinggasari, Jihan; Gimin, Gimin; Gani, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the effect of knowledge about Islamic banking and disposible income on interest in saving at BNI Syariah Bank Pekanbaru. The number of samples used in this study were 71 customers who made transactions at BNI Bank. The type of data used in this research is primary data in the form of knowledge, disposible income and interest in saving. The method of collecting data using a questionnaire. The analysis technique used in this research is multiple linear regression analysis. The results showed that there was a significant influence between knowledge and disposible income on the interest in saving at the new syariah Bank BNI.Key Words: Knowledge, Disposible income and Interest in saving